2017
DOI: 10.1101/229195
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Timeline of Brain Alterations in Alzheimer’s Disease Across the Entire Lifespan

Abstract: Brain imaging studies have shown that progressive cerebral atrophy characterized the development of Alzheimer's Disease (AD). The key question is howAlzheimer's disease (AD) is the most prevalent form of dementia in persons older than 65 years [1]. Cognitive impairment, mainly related to memory deficits, is the most common manifestation of this disease [2]. Available neuroimaging evidence suggests that the neuropathological alterations underlying AD probably begin much * Data used in preparation of this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
(61 reference statements)
1
3
0
Order By: Relevance
“…2 are remarkably similar to those from a recent meta-analysis with more than 100,000 HR isotropic scans (47): They correctly capture the peak of the white matter at about 30 years, the earlier decline of the gray matter, and the highly nonlinear trajectory of the ventricles. Despite using clinical scans with large spacing, our method also produces trajectories for subcortical ROIs that are highly consistent with previously published studies relying on thousands of 1-mm isotropic T1 scans (48,49), showing, e.g., earlier atrophy of the thalamus compared with hippocampus or amygdala.…”
Section: Image Segmentation and Volumetry With Existing Toolssupporting
confidence: 83%
“…2 are remarkably similar to those from a recent meta-analysis with more than 100,000 HR isotropic scans (47): They correctly capture the peak of the white matter at about 30 years, the earlier decline of the gray matter, and the highly nonlinear trajectory of the ventricles. Despite using clinical scans with large spacing, our method also produces trajectories for subcortical ROIs that are highly consistent with previously published studies relying on thousands of 1-mm isotropic T1 scans (48,49), showing, e.g., earlier atrophy of the thalamus compared with hippocampus or amygdala.…”
Section: Image Segmentation and Volumetry With Existing Toolssupporting
confidence: 83%
“…Replicating our earlier finding (Chao, 2020), veterans with MCI had smaller hippocampal volume compared to veterans with unimpaired cognition in this study. Previous longitudinal studies have reported morphometric difference in the hippocampi of incident AD cases at least 10 years prior to diagnosis (den Heijer et al, 2010;Bernard et al, 2014;Coupe et al, 2017). In a study that compared two models (normal and pathological) of brain aging, Coupe et al (2019) reported that the hippocampus was the first brain region to diverge from normal aging.…”
Section: Discussionmentioning
confidence: 97%
“…After a highly dynamic early postnatal period, brain growth stabilizes in adulthood, when interindividual differences become well established. These differences result from varying and nonlinear growth patterns in different brain structures throughout the lifespan (Coupé et al, 2017;Danielsen et al, 2020), leading to interindividual differences in brain volume, shape, development, and proportion between brain structures.…”
Section: Correlation Between Brain Volume and Stereotaxic Coordinatesmentioning
confidence: 99%